2021
DOI: 10.21037/jtd-20-2434
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model for identifying candidates for adjuvant chemotherapy based on recurrence risk profile of resected, node-negative (N0) non-small cell lung cancer

Abstract: Background:The decision for administering adjuvant chemotherapy (AC) in completely resected nodenegative non-small cell lung cancer (NSCLC) is guided by likelihood of disease recurrence or death based on tumor, node, metastasis (TNM) stage. However, within each TNM stage are sub-groups of patients that are more or less likely to relapse than stage alone predicts. Methods: In this retrospective cohort study, prospective data from 394 consecutive patients who underwent complete resection of node-negative NSCLC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…A comprehensive analysis based on data from The National Cancer Database, observed a survival benefit associated with ACT in patients with tumors 3 cm or larger and high-risk clinicopathological factors (10). Krivitsky et al constructed a risk stratification model for negative-node NSCLC and assigned 9% of stage I patients at high-risk who could be potential candidates for ACT (11). More interestingly, series studies demonstrated the improved survival associated with ACT even in stage IA patients with high-risk histopathological factors (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive analysis based on data from The National Cancer Database, observed a survival benefit associated with ACT in patients with tumors 3 cm or larger and high-risk clinicopathological factors (10). Krivitsky et al constructed a risk stratification model for negative-node NSCLC and assigned 9% of stage I patients at high-risk who could be potential candidates for ACT (11). More interestingly, series studies demonstrated the improved survival associated with ACT even in stage IA patients with high-risk histopathological factors (12,13).…”
Section: Introductionmentioning
confidence: 99%